A rapid screening method to evaluate the impact of nanoparticles on macrophages. Issue 7 (2nd February 2017) - Mottas, Inès; Milosevic, Ana; Petri-Fink, Alke; Rothen-Rutishauser, Barbara; Bourquin, Carole
Abstract : A rapid screening method to evaluate the impact of a panel of nanoparticles on macrophages: 3 tests are performed in parallel. Abstract : Nanotechnology is an emerging and highly promising field to develop new approaches for biomedical applications. There is however at present an unmet need for a rapid and universal method to screen nanoparticles (NP) for immunocompatibility at early stages of their development. Indeed, although many types of highly diverse NP are currently under investigation, their interaction with immune cells remains fairly unpredictable. Macrophages which are professional phagocytic cells are believed to be among the first cell types that take up NP, mediating inflammation and thus immunological responses. The present work describes a highly reproducible screening method to study the NP interaction with macrophages. Three essential questions are answered in parallel, in a single multiwell plate: Are the NP taken up by macrophages? Do the NP cause macrophage cell death? Do the NP induce inflammatory reactions? This assay is proposed as a standardized screening protocol to obtain a rapid overview of the impact of different types of NP on macrophages. Due to high reproducibility, this method also allows quality control assessment for such aspects as immune-activating contaminants and batch-to-batch variability.